2013
DOI: 10.1080/09670262.2013.852694
|View full text |Cite
|
Sign up to set email alerts
|

Data rich, information poor? Phytobenthos assessment and the Water Framework Directive

Abstract: The Water Framework Directive (WFD) provides the legal basis for water management in the European Union (EU). Twelve years after it was passed, all but five EU Member States had phytobenthos assessment methods for rivers, whilst nine had methods for lakes. Most are based on diatoms, although a few are supplemented by evaluations of non-diatoms and some include macroalgae as part of parallel macrophyte assessments. Norway is the exception, with assessment based on non-diatom algae alone. Over half of all states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 83 publications
1
49
0
2
Order By: Relevance
“…As case and comparative studies accumulated, doubts started to emerge about the overall applied methods and their appropriateness in assessing real ecological status. In his seminal paper, Kelly (2013) concluded that more Gomphonema parvulum (6.8%) Sp 5 Navicula gregaria (3.3%) , Na …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As case and comparative studies accumulated, doubts started to emerge about the overall applied methods and their appropriateness in assessing real ecological status. In his seminal paper, Kelly (2013) concluded that more Gomphonema parvulum (6.8%) Sp 5 Navicula gregaria (3.3%) , Na …”
Section: Discussionmentioning
confidence: 99%
“…One of the most robust arguments for using diatoms in ecological status assessment is their high species number. Although methods of status assessment from sampling to data analyses, including the applied indices, improved markedly, the underlying ecological knowledge has remained incomplete (Kelly, 2013). Until now, process-based research on relationships between environmental factors, population dynamics, and community attributes has been largely missing.…”
Section: Introductionmentioning
confidence: 99%
“…The US national bioassessments are largely based on diatom community composition, supplemented by total algal biomass data and proportional abundance of all algal taxonomic groups. Ecological integrity and ecological status are holistic concepts not confined to any single taxonomic group and require understanding of both the state of a particular indicator group and its interaction with other organisms and the catchment (Kelly, 2013). In theory, information gained from the entire benthic algal community can provide a more comprehensive indication of environmental conditions (Kelly, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The current state-of-art in algae-based river and stream bioassessment in the EU shows that the diatoms are developed and intercalibrated as proxies for phytobenthos, gradually narrowed to an application of a few diatom indices (Poikane, 2015). The softbodied algae supplement either phytobentos or macrophyte stream assessment systems in several states, and the abundance of the phytobentos is not evaluated (Kelly, 2013;Poikane, 2015). The only exception is Norway, whose stream bioassessment is based completely on soft-bodied algae (Schneider andLindstrøm, 2009, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these indices are mathematically identical to the transfer functions widely used in palaeolimnology to reconstruct variables such as total P (TP) (e.g., Bennion et al 1996, Hall andSmol 2010). However, the objective of contemporary assessment is not to provide a proxy for a variable that can be measured relatively easily, but to distill biological information into a value that can be related to biological condition (Kelly 2011(Kelly , 2013.…”
mentioning
confidence: 99%